Early Diastolic Peak Velocity of Mitral Valve Annulus and Right Ventricular Systolic Tricuspid Annular Velocity as Predictors in Assessing Prognosis of Patients with Sepsis - Lu NF; Shao J; Niu HX; Han WY; Chen YL; Liu AQ; Liu HN; Xi XM (Dove Medical Press, 2023)
Nian-Fang Lu,1 Jun Shao,2 Hong-Xia Niu,3 Wen-Yong Han,4 Ya-Lei Chen,1 An-Qi Liu,1 Hu-Nan Liu,1 Xiu-Ming Xi5 1Department of Critical Care Medicine, Capital Medical University Electric Teaching Hospital/Beijing Electric Power Hospital, Beijing, 100073, People's Republic of China; 2Department of Critical Care Medicine, Subei People's Hospital of Jiangsu Province, Yangzhou, Jiangsu, 225001, People's Republic of China; 3Department of Emergency, Capital medical university electric teaching hospital/Beijing Electric Power Hospital, Beijing, 100073, People's Republic of China; 4Department of Anesthesiology, Capital Medical University Electric Teaching Hospital/Beijing Electric Power Hospital, Beijing, 100073, People's Republic of China; 5Department of Critical Care Medicine, Capital Medical University Fuxing Hospital, Beijing, People's Republic of ChinaCorrespondence: Xiu-Ming Xi, Department of Critical Care Medicine, Capital Medical University Fuxing Hospital, A 20, Fuxingmenwai Street, Xicheng District, Beijing, People's Republic of China, Tel +86 010 13801244610, Email xixuimingxxm@126.comObjective: To analyze the epidemiological data of patients with septic cardiomyopathy and investigate the relationship between ultrasonic parameters and prognosis of patients with sepsis.Methods: In this study, we enrolled patients with sepsis who were treated at the Department of Critical Care Medicine in the Beijing Electric Power Hospital (No.1 Taipingqiao Xili, Fengtai District, Beijing) from January 2020 to June 2022. All patients received standardized treatment. Their general medical status and 28-day prognosis were recorded. Transthoracic echocardiography was performed within 24 hours after admission. We compared the ultrasound indexes between the mortality group and the survival group at the end of 28 days. We included parameters with significant difference in the logistic regression model to identify the independent risk factors for prognosis and evaluated their predictive value using receiver operating characteristic (ROC) curve.Results: We included 100 patients with sepsis in this study; the mortality rate was 33% and the prevalence rate of septic cardiomyopathy was 49%. The peak e' velocity and right ventricular systolic tricuspid annulus velocity (RV-Sm) of the survival group were significantly higher than those of the mortality group (P < 0.05). Results of logistic regression analysis showed that the peak e' velocity and RV-Sm were independent risk factors for prognosis. The area under curve of the peak e' velocity and the RV-Sm was 0.657 and 0.668, respectively (P < 0.05).Conclusion: The prevalence rate of septic cardiomyopathy in septic patients is high. In this study, we found that the peak e' velocity and right ventricular systolic tricuspid annulus velocity were important predictors of short-term prognosis.Keywords: peak e' velocity by tissue Doppler imaging, prognosis, right ventricular systolic tricuspid annulus velocity, septic cardiomyopathy